(untitled) (Journal of Nuclear Technology in Applied Science, 2021)
Handling and manipulation of biological cells are fundamental for biotechnology applications like genes modification, membrane fusion, and drug researches. Cells in suspension can be handled by external applied force fields. This force can be immunological mainly depends on membrane binding criteria of living cells, or non-immunological methods utilize physical properties such as, cell size and shape. Hereby, dry baker’s yeast cells suspension were handled by the aid of simple homemade ultrasonic standing wave chamber operate at frequency 0.8 MHz, power intensities ranged of 0.5-3 W/cm2 in pulsed mode. Microscopic monitoring revealed cells trapping in nearly ultrasonic wave’s interference nodes by the acoustic radiation forces. The effect acoustic on trapping time and velocity of the cell was investigated. The trapping behavior depends mainly on the cell size, ultrasound power intensity. Increasing the ultrasound intensity decreases the time consumed to trap cells. In summary, acoustic forces generated in standing wave mode may be a simple promising non invasive tool for biological cell handling for more biotechnology applications.